2018
DOI: 10.1016/j.foodchem.2018.02.074
|View full text |Cite
|
Sign up to set email alerts
|

Combination of sodium caseinate and succinylated alginate improved stability of high fat fish oil-in-water emulsions

Abstract: Sodium caseinate (CAS) and commercial sodium alginate (CA), long chain modified alginate (LCMA) or short chain modified alginate (SCMA) were used in combination for emulsifying and stabilizing high fat (50-70%) fish oil-in-water emulsions. Physical (creaming, droplet size, viscosity and protein determination) and oxidative (primary and secondary oxidation products) stabilities of the emulsions were studied during 12 days of storage. Creaming stability was higher for emulsions produced with alginates and CAS co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
(43 reference statements)
3
18
0
Order By: Relevance
“…Based on the results reported in Figure 6, we fund that the inter- size and higher viscosity (Yesiltas et al, 2018). Due to the long chain in the oil phase, the SNEs with higher apparent viscosity improved physically stable.…”
Section: Solubility Study Interfacial Tension and Apparent Viscositysupporting
confidence: 52%
“…Based on the results reported in Figure 6, we fund that the inter- size and higher viscosity (Yesiltas et al, 2018). Due to the long chain in the oil phase, the SNEs with higher apparent viscosity improved physically stable.…”
Section: Solubility Study Interfacial Tension and Apparent Viscositysupporting
confidence: 52%
“…Anisidine value, which is the primary indicator depicting the formation of secondary oxidation products also showed the similar trend. This indicated the exposure of the unencapsulated HWO to atmospheric oxygen [45] . Amongst the formulations M2-M5, there was no significant difference (p > 0.05) in the formation of hydroperoxides between them during the course of storage until the final day of analysis.…”
Section: Resultsmentioning
confidence: 97%
“…Same characteristics were also reported by Yesiltas et al for high fat oil-in-water emulsions stabilized with CAS and alginates. 32 Apparent viscosity of the samples showed that 60% replacement of the DATEM with modified DATEMs provided significantly less viscous emulsions. This was the case also for the emulsions which had 10% of its DATEM replaced by DATEM C14.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 96%
“…Secondary Oxidation Products: Dynamic Head Space GC-MS. Volatile secondary oxidation products were analyzed according to the method described by Yesiltas et al 32 Emulsion samples (approximately 4 g) were mixed with 2 mL of antifoam and 10 mL of distilled water in a 100 mL purge bottle. The bottle was heated in a water bath at 60 °C while purging with nitrogen (flow 150 mL/min, 30 min).…”
Section: Emulsion Preparation and Samplingmentioning
confidence: 99%